The Chicago manual of style. (Chicago : The University of Chicago Press, 2010)
Provides information on manuscript preparation, punctuation, spelling, quotations, captions, tables, abbreviations, references, bibliographies, notes, and indexes, with sections on journals and electronic media.
The publishing process -- Books and journals -- Overview -- The parts of a book -- The parts of a journal -- Considerations for web-based publications -- Manuscript preparation, manuscript editing, and proofreading -- Overview and process outline -- Manuscript preparation guidelines for authors -- Manuscript editing -- Proofreading -- Illustrations and tables -- Overview -- Illustrations -- Tables -- Rights, permissions, and copyright administration / by William S. Strong -- Overview -- Copyright law and the licensing of rights -- The publishing agreement -- Subsidiary rights and permissions -- The author's responsibilities -- Style and usage -- Grammar and usage / by Bryan A. Garner -- Grammar -- Word usage -- Punctuation -- Overview -- Punctuation in relation to surrounding text -- Periods -- Commas -- Semicolons -- Colons -- Question marks -- Exclamation points -- Hyphens and dashes -- Parentheses -- Brackets and braces -- Slashes -- Quotation marks -- Apostrophes -- Multiple punctuation marks -- Lists and outline style -- Spelling, distinctive treatment of words, and compounds -- Overview -- Plurals -- Possessives -- Contractions and interjections -- Word division -- A and an, o and oh -- Ligatures -- Italics, capitals, and quotation marks -- Compounds and hyphenation -- Names and terms -- Overview -- Personal names -- Titles and offices -- Epithets, kinship names, and personifications -- Ethnic, socioeconomic, and other groups -- Names of places -- Words derived from proper names -- Names of organizations -- Historical and cultural terms -- Calendar and time designations -- Religious names and terms -- Military terms -- Names of ships and other vehicles -- Scientific terminology -- Brand names and trademarks -- Titles of works -- Signs and mottoes -- Numbers -- Overview -- Numerals versus words -- Plurals and punctuation of numbers -- Inclusive numbers -- Roman numerals -- Abbreviations -- Overview -- Names and titles -- Geographical terms -- Designations of time -- Scholarly abbreviations -- Biblical abbreviations -- Technology and science -- Business and commerce -- Foreign languages -- Overview -- Titles and other proper names -- Languages using the Latin alphabet -- Languages usually transliterated (or romanized) -- Classical Greek -- Old English and middle English -- American Sign Language -- Mathematics in type -- Overview -- Style of mathematical expressions -- Preparation and editing of paper manuscripts -- Quotations and dialogue -- Overview -- Permissible changes to quotations -- Quotations in relation to text -- Quotation marks -- Ellipses -- Interpolations and clarifications -- Citing sources in text -- Foreign-language quotations -- Documentation -- Documentation I. Notes and bibliography. Source citations : an overview ; Notes and bibliography : basic format, with examples and variations ; Notes ; Bibliographies ; Books ; Periodicals ; Interviews and personal communications ; Unpublished and informally published material ; Special types of references ; Audiovisual materials ; Legal and public documents ; Documentation II. Author-date references. Overview ; Author-date references : basic format, with examples and variations ; Reference lists and text citations ; Author-date references : special cases -- Indexes. Overview ; Components of an index ; General principles of indexing ; Indexing proper names and variants ; Indexing titles of publications and other works ; Alphabetizing ; Punctuating indexes : a summary ; The mechanics of indexing ; Editing an index compiled by someone else ; Typographical considerations for indexes ; Examples of indexes -- Appendix A. Production and digital technology. Overview ; Markup ; Design ; The electronic workflow ; Options for presenting content ; Print technologies -- Appendix B. Glossary.
Includes bibliographical references (p. [907]-924) and index.
Keywords: Printing -- Style manuals; Authorship -- Style manuals; Publishing; Authorship; Writing